Publish or Perish: still a concern ? - Resti Tito VILLARINO; Aslı Gül ÖNCEL; Lili ZHENG; Angeline M. POGOY; Filomena DAYAGBIL; Michel PLAISENT (Communications of International Proceedings, 2025)
The imperative to “publish or perish,” first introduced in 1932 and popularized by Eugene Garfield in 1996, reflects the increasing pressure on academics to produce research for career advancement and institutional recognition. In the context of academic capitalism and the marketization of higher education, research output has become a key competitive tool for universities seeking prestige, funding, and accreditation. However, this emphasis on publication—particularly in high-impact, English-language journals—raises concerns about research quality, academic equity, and the marginalization of teaching and regional knowledge. This paper explores the complex dynamics of research productivity, focusing specifically on publication output as its most common proxy. Drawing on an extensive literature review and empirical findings from a large-scale exploratory study, the paper identifies key motivators and barriers that influence faculty publication behavior. These include institutional pressures, accreditation demands, workload imbalances, and global inequalities in research support and visibility. By analyzing these factors, the study aims to inform higher education institutions in developing targeted strategies that foster meaningful research engagement among faculty, while promoting a more balanced, inclusive, and sustainable academic environment.
Keywords: Research productivity; publish or perish; academic culture; higher education policy